24-h dietary intake and its relationship with nutritional knowledge and behaviors in older adults with type 2 diabetes in Vietnam - Truong, Duong Thuy Thi; Nguyen, Hoa Thi; Le, Hoa Thanh Thi (Frontiers in Nutrition, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is a growing public health challenge in Vietnam, particularly among older adults, with dietary intake critical for its management. Limited research explores how nutritional knowledge and dietary behaviors influence dietary intake in Vietnamese older adults with T2DM.ObjectiveThis study assesses 24-h dietary intake and its relationship with nutritional knowledge and dietary behaviors in older adults with T2DM in Vietnam.MethodsA cross-sectional study was conducted among 355 older adults with T2DM at Vinh Yen City Medical Center, Vinh Phuc, Vietnam. Data included anthropometric measurements, biochemical parameters, and 24-h dietary recall. Nutritional knowledge and dietary behaviors were assessed via structured questionnaires. Regression analyses examined associations with glycemic control.ResultsOverweight/obese participants had significantly higher energy (1,331.1 kcal/day vs. 1,104.9 kcal/day, P < 0.001), protein (74.2 g/day vs. 59.9 g/day, P < 0.001), carbohydrate (199.2 g/day vs. 168.9 g/day, P = 0.022), and fat intake (26.4 g/day vs. 21.1 g/day, P = 0.034) than normal-weight participants. Poor nutritional knowledge was prevalent in 51% of overweight/obese vs. 19% of normal-weight participants (P < 0.001), with only 16.3% adhering to dietary guidelines. Higher energy intake was associated with increased HbA1c (β = 0.15, P = 0.049), while carbohydrate intake showed an inverse relationship (β = −0.60, P = 0.049). Higher BMI was linked to lower HbA1c (β = −0.15, P = 0.029).ConclusionOlder adults with T2DM in Vietnam show significant variations in dietary intake, with poor nutritional knowledge, and low dietary adherence, particularly among overweight/obese individuals. Poor dietary adherence and limited nutritional understanding, particularly among overweight/obese individuals, highlight the need for targeted dietary interventions. Structured nutritional counseling and culturally tailored education programs may improve adherence and glycemic control in this population. Interventions are needed to address barriers like limited knowledge and economic constraints, thereby improving glycemic control and informing public health policies.